Answer:
Step-by-step explanation:
f(-5) = -5 + 8 = 3
g(3) = 3^3 = 27
Answer:
![\large\boxed{y=\dfrac{3}{2}x-1}](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7By%3D%5Cdfrac%7B3%7D%7B2%7Dx-1%7D)
Step-by-step explanation:
The slope-intercept form of an equation of a line:
![y=mx+b](https://tex.z-dn.net/?f=y%3Dmx%2Bb)
<em>m</em><em> - slope</em>
<em>b</em> - <em>y-intercept</em>
We have
![m=\dfrac{3}{2},\ b=-1](https://tex.z-dn.net/?f=m%3D%5Cdfrac%7B3%7D%7B2%7D%2C%5C%20b%3D-1)
Substitute:
![y=\dfrac{3}{2}x+(-1)=\dfrac{3}{2}x-1](https://tex.z-dn.net/?f=y%3D%5Cdfrac%7B3%7D%7B2%7Dx%2B%28-1%29%3D%5Cdfrac%7B3%7D%7B2%7Dx-1)
3(x+2)+11>20
minus 11 both sides
3(x+2)>9
divide both sides by 3
x+2>3
minus 2 both sides
x>1
Answer:
Therefore the required polynomial is
M(x)=0.83(x³+4x²+16x+64)
Step-by-step explanation:
Given that M is a polynomial of degree 3.
So, it has three zeros.
Let the polynomial be
M(x) =a(x-p)(x-q)(x-r)
The two zeros of the polynomial are -4 and 4i.
Since 4i is a complex number. Then the conjugate of 4i is also a zero of the polynomial i.e -4i.
Then,
M(x)= a{x-(-4)}(x-4i){x-(-4i)}
=a(x+4)(x-4i)(x+4i)
=a(x+4){x²-(4i)²} [ applying the formula (a+b)(a-b)=a²-b²]
=a(x+4)(x²-16i²)
=a(x+4)(x²+16) [∵i² = -1]
=a(x³+4x²+16x+64)
Again given that M(0)= 53.12 . Putting x=0 in the polynomial
53.12 =a(0+4.0+16.0+64)
![\Rightarrow a = \frac{53.12}{64}](https://tex.z-dn.net/?f=%5CRightarrow%20a%20%3D%20%5Cfrac%7B53.12%7D%7B64%7D)
=0.83
Therefore the required polynomial is
M(x)=0.83(x³+4x²+16x+64)
#9 the sum of two angles is 90 degrees, creating a right angle.
#10 the sum of the two angles is 180 because the form a supplementary angle